Reaction pathways in the gas phase negative ion chemistry of chlorinated ethenes - Kennedy, R; Mayhew, C; Peverall, R; Watts, P (2000)
The reaction rate coefficients and ion products for the gas-phase reactions of O2-,O-, OH-, CF3-, and F- with trichloroethene (CCl2=CHCl), 1,1-dichloroethene (CH2=CCl2), and Z (cis) and E (trans)-1,2-dichloroethene (CHCl=CHCl) are presented. With the exception of CCl2=CHCl, the O2- bimolecular reaction rate coefficients are substantially below the collisional values. All the other anions react with the molecules with rate coefficients at or close to (within a factor of two) the corresponding collisional values. The experimental results are interpreted in terms of pathways initiated by nucleophilic attack on carbon or by proton abstraction. Proton abstraction is an exothermic channel for the reactions of O-, OH-, CF3-, and F- with each of the three isomers of dichloroethene, but C2HCl2- was only directly observed for E-CHCl=CHCl. Orbital overlap arguments provide the explanation of this observation.